S100A4 promotes the development of lipopolysaccharide-induced mouse endometritis. Issue 5 (24th May 2018) - Wu, Yingjie; Zhang, Jinhua; Qin, Yinghe
Abstract: S100A4 is suggested to be a critical regulator of tumor metastasis, and implicated in progression of inflammation. The aim of this study is to investigate the expression and possible role of S100A4 in endometritis. Using a mouse model of endometritis induced by local injection of lipopolysaccharide (LPS), we found that infection induced recruitment of S100A4-positive cells in the endometrium of wild-type mice. Deficiency of S100A4 reduced uterine pathological reaction and mRNA expression of proinflammatory cytokine IL-1β and TNF-α ( P  < 0.01), suggesting S100A4 promoted the progression of endometritis. To further explore the potential mechanism, we examined the cellular proliferation and apoptosis in the endometrium. Western blot and immunohistochemical results showed that cell apoptosis in uterus during endometritis, marked by cleaved-Caspase 3 protein, was significantly cut down in S100a4 −/− mice; cell proliferation, which was indicated by Ki-67, was also significantly decreased in the inflamed endometrial stroma of S100a4 −/− mice. Overall, these results demonstrate that S100A4 promotes the development of LPS-induced endometritis, and it may be related to the process of cell proliferation and apoptosis during the inflammation. Abstract : S100A4, which was increased in LPS-infected mouse endometrium, contributes to the development of endometritis.